2013
DOI: 10.1179/1973947812y.0000000067
|View full text |Cite
|
Sign up to set email alerts
|

Difference in nephrotoxicity of vancomycin administered once daily and twice daily in rats

Abstract: We compared the degree of nephrotoxicity of vancomycin (VCM) administered once daily and twice daily in rats. VCM was intraperitoneally administered once daily to rats at a dose of 400 mg/kg (VCM-1-treated) or administered at a dose of 200 mg/kg twice daily at 12-hour intervals (VCM-2-treated) for 7 consecutive days. Creatinine clearance was decreased more markedly in VCM-1 rats relative to VCM-2 rats, although there was no significant difference in renal accumulation of VCM between the two groups. Renal super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…To date, animal models of AKI have confirmed that vancomycin is a nephrotoxin. Dose-ranging studies have revealed that an increase in the vancomycin dose and an increase in the duration of treatment in rats are associated with increases in histopathological damage and elevations in novel urinary biomarkers of AKI (8)(9)(10). However, a prospectively derived ex-posure-AKI (i.e., a pharmacokinetic [PK]/toxicodynamic [TD]) threshold for vancomycin has not been defined.…”
mentioning
confidence: 99%
“…To date, animal models of AKI have confirmed that vancomycin is a nephrotoxin. Dose-ranging studies have revealed that an increase in the vancomycin dose and an increase in the duration of treatment in rats are associated with increases in histopathological damage and elevations in novel urinary biomarkers of AKI (8)(9)(10). However, a prospectively derived ex-posure-AKI (i.e., a pharmacokinetic [PK]/toxicodynamic [TD]) threshold for vancomycin has not been defined.…”
mentioning
confidence: 99%
“…Changes in body and kidney weights are valuable indicators of severe renal toxicity in the experimental models (6,8,9,33). In our experimental condition, VCM caused a significant reduction in the body weight and increased the ratio of average kidneys to 100 g body weight.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, phenolic and flavonoid contents of NOE detected to be 71 ± 6.23 gallic acid equivalents/g dried extract and 95.26 ± 7.6 mg rutin equivalents/g dried extract, respectively. Based on 6 Jundishapur J Nat Pharm Prod. In Press(In Press):e67178.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations